AB0734 Assessment of Spondyloarthritis Patients Bone Health by Trabecular Bone Score (TBS): A Pilot Study. (10th June 2014) - Boiadjieva, V.; Wildberger, L.; Stoilov, N.; Hans, D.; Ivanova, M.; Stoilov, R.; Aubry Rozier, B.; Rashkov, R.
Abstract : Background: Patients with spondyloarthritis (SpA) have an elevated incidence of osteoporosis and are at increased risk of pathological vertebral fracture. Evaluation of bone by dual energy X-Ray absorptiometry (DXA) has its limits in fracture prediction, as it only measures quantity, but not quality of bone. Trabecular bone score (TBS) is a new texture measurement correlated with bone microarchitecture. Objectives: We aimed to describe a male and female population of SpA with BMD and TBS evaluation and study the relationship between bone health parameters and rheumatic disease activity. Methods: 2 cohorts of SpA patients (Lausanne, Sofia) with SpA disease parameters (clinical assessments with disease-specific measurements) and bone parameters (femoral and total spine BMD + spine TBS) were merged. We separated female and male. We compared both BMD and TBS results to young normative values and study their relationships with the disease activity, physical function and spinal mobility. Disease activity was assessed by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the preferred version of ASDAS (ASDAS-CRP). Physical function was measured by the Bath Ankylosing Spondylitis Functional Index (BASFI) and spinal mobility - by the Bath Ankylosing Spondylitis Metrology Index (BASMI). All patients were ESSG, 100% of men and 92% of women ASAS positive. The patients with chronic renal diseases, chronic use of high doses of corticosteroids, endocrine diseases (hyperparathyroidism) or chronic alcohol abuse were excluded from the study. Results: 49 females, 41 males. For population characteristics, see Table 1 Only Spine TBS and femoral BMD T-score were significantly correlated with the BASMI index. The other correlations with Disease activity and function did not reach the significance level. Conclusions: Men tend to have weaker bone health than women at the same age in this study. Such difference could be explained by the higher disease activity and clinical risk factors and the lower level of OP treatment in men than women. Further statistical analyses are underway on the entire cohort. Both BMD and TBS results of SpA patients are lower than young normative values which would be consistent with higher fracture risk. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4235